Gender-Based Preconception Screening Service Skills Training for Posyandu Cadres - Nurasiah, Ai; Asrina, A; Indrayani, Indrayani; Apriliani, Lia; Nisrina, Resna Fatin; Jaziroh, Fadla Yahlil (Poltekkes Kemenkes Surakarta, 2025)
Background: Preconception services play an important role in preventing pregnancy risks and improving the health of the mother and baby. However, its utilization in rural communities is still low, including the involvement of male couples. Posyandu cadres have the potential to become drivers of preconception screening if they are equipped with gender-responsive training. Quantitative evidence of improving cadre skills through training at the village level is still limited. The purpose of this community service is to improve the ability of posyandu cadres in preconception screening services. Methods: This community service was carried out in Cikadu Village, Kuningan Regency, in August 2025 with a target of 35 Posyandu cadres. Training activities were carried out for one day, including pre-test, delivery of materials (basic concepts of preconception health, preconception risk factors, gender concepts in preconception services, effective communication, and gender-based counseling and preconception screening services), and simulation of preconception screening practices using preconception and post-test screening checklists. The media used during the training are training modules, pocket books, and leaflets. Results: The average (±SD) preconception screening skill score increased from 105.29±23.93 (pretest) to 120.69±30.60 (posttest), indicating an improvement in practical competence after training. Conclusion: Posyandu cadre training is effective in improving gender-based preconception screening skills. It is hoped that preconception services can be integrated into the regular posyandu program with the support of the health center and the husband's involvement strategy